Snake venom derived fibrin adhesive in dog uterine healing: biomechanical study - Moraes, J. R. E. [UNESP]; Camplesi, A. C. [UNESP]; Correia, P. H. A. [UNESP]; Shimano, A. C. [UNESP]; Ferraro, G. C. [UNESP]; Moraes, F. R. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos, 2005)
Healing is a complex process with many interfering factors. The objective of this work was to evaluate regeneration strength of non-pregnant adult dog uterus when snake venom derived fibrin adhesive is used to reinforce hysterorrhaphy. Maximum limit and rigidity were analyzed. Twenty uterine horns from 10 dogs were hysterotomized and distributed into 2 equal groups. Hysterorrhaphy was performed using the Shimieden-Cushing double layer suture. In one group, animals received snake venom derived fibrin adhesive as reinforcement. Although neither variable was significantly different, our results showed higher rigidity values in the adhesive group. This can be attributed to the adhesive’s effect on organ elasticity or to more granulation tissue formed in the uterine scar.
Keywords: biomechanical properties; healing; dog uterus; fibrin adhesive; snake venom